Higher‐Order Topological States in Thermal Diffusion. Issue 14 (21st February 2023) - Wu, Haotian; Hu, Hao; Wang, Xixi; Xu, Zhixia; Zhang, Baile; Wang, Qi Jie; Zheng, Yuanjin; Zhang, Jingjing; Cui, Tie Jun; Luo, Yu
Abstract: Unlike conventional topological materials that carry topological states at their boundaries, higher‐order topological materials are able to support topological states at boundaries of boundaries, such as corners and hinges. While band topology has been recently extended into thermal diffusion for thermal metamaterials, its realization is limited to a 1D thermal lattice, lacking access to the higher‐order topology. In this work, the experimental realization is reported of a higher‐order thermal topological insulator in a generalized 2D diffusion lattice. The topological corner states for thermal diffusion are observed in the bandgap of diffusion rate of the bulk, as a consequence of the anti‐Hermitian nature of the diffusion Hamiltonian. The topological protection of these thermal corner states is demonstrated with the stability of their diffusion profile in the presence of amorphous deformation. This work constitutes the first realization of higher‐order topology in purely diffusive systems and opens the door for future thermal management with topological protection beyond 1D geometries. Abstract : Experimental realization of higher‐order thermal topological states in a generalized 2D diffusion lattice is reported. The topological edge and corner states for thermal diffusion are observed in the bandgap of diffusion rate spectrum that isolated from the bulk. Topological protection of these thermal domain‐wall states is demonstrated with the stability of their diffusion profiles in the presence of amorphous deformation.